Pengaruh Kualitas Layanan Mobile Banking (M-Banking) Terhadap Kepuasan Nasabah di Indonesia [Effect of Mobile Banking (M-Banking) Service Quality on Customer Satisfaction in Indonesia] - Aditya Wardhana (DeReMa (Development Research of Management): Jurnal Manajemen, 2015)
The research aim was to assess the influence of the service quality of mobile banking (m-banking) against customer satisfaction at the greatest banks in Indonesia. Elements of the quality of mobile banking services (m-banking) were speed, security, accuracy, and trust. The population of this study was bank customers from eight of the greatest bank in Indonesia -- Bank Mandiri, Bank BRI, Bank BCA, Bank BNI, Bank CIMB Niaga, Bank Danamon, Bank Permata, and Bank Panin -- who used mobile banking which totaled 19.9 million customers with the size of the sample being 400 respondents. The sampling method used nonprobability sampling by incidental sampling. The results by using a structural equation modeling (SEM) found significant influences between service quality of mobile banking (m-banking) partially and simultaneously to customer satisfaction.